Cultural landscape and tourism potential of Taiwan’s old mountain railway: a SWOT-FANP approach to sustainable heritage management - Ling-Zhong Lin; Tsung-Yin Ou (Cogent Business & Management)
The sustainable development of railway cultural heritage requires leveraging tourism activities to create business opportunities and establish long-term tourism resources. The cultural landscape surrounding Taiwan’s Old Mountain Railway, which is rich in cultural assets and natural scenery, plays a pivotal role in the nation’s tourism development. This study introduces an integrated approach to advancing railway culture by designing a program to assess the importance, performance, and execution priorities of experiential marketing strategies. Eleven strategic plans are proposed, focusing on activities aligned with the four key dimensions of experiential marketing: “senses/association,” “emotion/association,” “thinking/association,” and “mobile/association.” To prioritize these plans, the study utilizes a SWOT matrix for analysis, which is supported by the fuzzy analytic network process (FANP) and importance–performance analysis (IPA). Through the application of this integrated assessment framework, this study evaluates both the internal and external conditions of the Old Mountain Railway and underscores the strategic significance of railway cultural development in practice.